Effect of iron and zinc-biofortified pearl millet consumption on growth and immune competence in children aged 12–18 months in India: study protocol for a randomised controlled trial. Issue 11 (14th November 2017) - Mehta, Saurabh; Finkelstein, Julia L; Venkatramanan, Sudha; Huey, Samantha L; Udipi, Shobha A; Ghugre, Padmini; Ruth, Caleb; Canfield, Richard L; Kurpad, Anura V; Potdar, Ramesh D; Haas, Jere D
Abstract : Introduction: Biofortified crops represent a sustainable agricultural solution for the widespread micronutrient malnutrition in India and other resource-limited settings. This study aims to investigate the effect of the consumption of foods prepared with iron- and zinc-biofortified pearl millet (FeZn-PM) by children on biomarkers of iron and zinc status, growth, and immune function. Methods and analysis: We will conduct a randomised controlled feeding trial in identified slums of Mumbai, India among 200 children aged between 12 and 18 months. Children will be randomised to receive foods prepared with the biofortified PM (FeZn-PM, ICTP8203-Fe) or non-biofortified PM. Anthropometric and morbidity data will be gathered every month for 9 months. Biological samples will be collected at baseline, midline and endline to assess iron and zinc status, including haemoglobin, serum ferritin, serum transferrin receptor, serum zinc, C-reactive protein and alpha-1 acid glycoprotein. Biological samples will be archived for future analyses. The midline measurement will be a random serial sample between baseline and endline. Immune function will be assessed at each time point by the measurement of T cell counts and vaccine responses in a subset, respectively. Ethics and dissemination: This study has obtained clearance from the Health Ministry Screening Committee of the Indian Council of Medical Research. Ethical clearance has been obtained from Cornell University's Institutional Review Board, the Inter System Biomedica Ethics Committee and St John's Research Institute's Institutional Ethics Review Board. The results of this study will be disseminated at several research conferences and as published articles in peer-reviewed journals. Trial registration number: Clinical trial registration number NCT02233764 . CTRI registration number REF/2014/10/007731.